What's in a name? That which we call Multiple Sclerosis Fatigue. (June 2021) - Hubbard, Amy Lynn; Golla, Heidrun; Lausberg, Hedda
Very limited progress has been made to date in the treatment of debilitating Multiple Sclerosis (MS) daily onset symptoms. These daily symptoms include motor, sensory, and cognitive impairments as well as an overwhelming feeling of tiredness, often referred to as "MS fatigue." Although widely cited as a main cause of inability to work and poor quality of life in patients with MS, daily onset MS-related tiredness continues to defy definition, and, consequently, measurement and treatment. Beginning with a historical overview of observations of daily onset MS-related tiredness, this Topical Review demonstrates how the misnomer "MS fatigue" has introduced ongoing misunderstanding for patients, investigators, clinicians, and therapists. Finally, combining current findings in clinical neuroscience with the striking set of long-standing commonalities present throughout the past 200 years of clinical observations, we underscore the immediate necessity for conceptual and applied change, to be initiated by the renaming of this distinct syndrome.